34.0k views
1 vote
HELP PLEASE! 13 POINTS!! {simplify (3x - 8) + (2x + 5) - (4x - 8).}

(A) x + 21
(B) 9x - 11
(C) 9x + 5
(D) x - 11
(E) x + 5

1 Answer

1 vote
First, let's start by adding the first two terms: (3x - 8) + (2x + 5) = (3x + 2x) + (5 - 8) = 5x + (-3) = 5x - 3

Then we can combine this result with the third term: (5x - 3) - (4x - 8) = (5x - 4x) + (-3 - (-8)) = x + (-3 - (-8)) = x + 5

Therefore, the simplified expression is: x + 5.

The answer is therefore (E) x + 5.
User Tyler Liu
by
7.5k points